Patterns of energy availability of free-living athletes display day-to-day variability that is not reflected in laboratory-based protocols: Insights from elite male road cyclists. Issue 16 (18th August 2022) - Taylor, Harry L.; Garabello, Giacomo; Pugh, Jamie; Morton, James; Langan-Evans, Carl; Louis, Julien; Borgersen, Reidar; Areta, Jose L.
ABSTRACT: The physiological effects of low energy availability (EA) have been studied using a homogenous daily EA pattern in laboratory settings. However, whether this daily EA pattern represents those of free-living athletes and is therefore ecologically valid is unknown. To investigate this, we assessed daily exercise energy expenditure, energy intake and EA in 10 free-living elite male road cyclists (20 min Mean Maximal Power: 5.27 ± 0.25 W · kg −1 ) during 7 consecutive days of late pre-season training. Energy intake was measured using the remote-food photography method and exercise energy expenditure estimated from cycling crank-based power-metres. Seven-day mean ± SD energy intake and exercise energy expenditure was 57.9 ± 10.4 and 38.4 ± 8.6 kcal · kg FFM −1 · day −1, respectively. EA was 19.5 ± 9.1 kcal · kg FFM −1 · day −1 . Within-participants correlation between daily energy intake and exercise energy expenditure was .62 (95% CI: .43 – .75; P < .001), and .60 (95% CI: .41 – .74; P < .001) between carbohydrate intake and exercise energy expenditure. However, energy intake only partially compensated for exercise energy expenditure, increasing 210 kcal · day −1 per 1000 kcal · day −1 increase in expenditure. EA patterns displayed marked day-to-day fluctuation (range: −22 to 76 kcal · kg FFM −1 · day −1 ). The validity of research using homogenous low EA patterns therefore requires further investigation.